The requirement for eukaryotic initiation factor 4A (eIF4A) in translation is in direct proportion to the degree of mRNA 5′ secondary structure - SVITKIN, YURI V.; PAUSE, ARNIM; HAGHIGHAT, ASHKAN; PYRONNET, STÉPHANE; WITHERELL, GARY; BELSHAM, GRAHAM J.; SONENBERG, NAHUM (RNA (Cambridge), 2001)
Eukaryotic initiation factor (eIF) 4A functions as a subunit of the initiation factor complex eIF4F, which mediates the binding of mRNA to the ribosome. eIF4A possesses ATPase and RNA helicase activities and is the prototype for a large family of putative RNA helicases (the DEAD box family). It is thought that the function of eIF4A during translation initiation is to unwind the mRNA secondary structure in the 5′ UTR to facilitate ribosome binding. However, the evidence to support this hypothesis is rather indirect, and it was reported that eIF4A is also required for the translation of mRNAs possessing minimal 5′ UTR secondary structure. Were this hypothesis correct, the requirement for eIF4A should correlate with the degree of mRNA secondary structure. To test this hypothesis, the effect of a dominant-negative mutant of mammalian eIF4A on translation of mRNAs with various degrees of secondary structure was studied in vitro. Here, we show that mRNAs containing stable secondary structure in the 5′ untranslated region are more susceptible to inhibition by the eIF4A mutant. The mutant protein also strongly inhibits translation from several picornavirus internal ribosome entry sites (IRES), although to different extents. UV crosslinking of eIF4F subunits and eIF4B to the mRNA cap structure is dramatically reduced by the eIF4A mutant and RNA secondary structure. Finally, the eIF4A mutant forms a more stable complex with eIF4G, as compared to the wild-type eIF4A, thus explaining the mechanism by which substoichiometric amounts of mutant eIF4A inhibit translation.